An exploration of corporate real estate management outsourcing practices in South Africa - Modise, Tapiwa P (Department of Construction Economics and Management, 2019)
Purpose – The considerations of non-real estate private organisations in South Africa when outsourcing their corporate real estate management (CREM) functions are examined. The investigation seeks to determine the elements that impact the decision to outsource CREM functions; the characteristics looked for in service providers and if there is a mismatch between what corporate entities desire from CREM outsourcing and what service providers deliver. Design – The study is grounded on a broad analysis of the literature globally and locally; as well as data collected through semi-structured interviews to build four (4) case studies; to gather information about a small set of organisations, within the Johannesburg Metropolitan area of South Africa, on their CREM outsourcing activities. Inductive content analysis will be used to analyse the data collected. Findings – All the organisations outsource parts of their CREM. However, the incidence of CREM outsourcing has neither increased nor decreased in the last three (3) years. Four (4) CREM services are outsourced; facilities management is the most frequently outsourced, followed by subject matter expertise in second and real estate management and transaction management in joint third. The majority of the organisations adhere to a global outsourcing strategy, as opposed to a local or no strategy. Correspondingly, the majority of the organisations have a formal guideline. Seven (7) motives or drivers for CREM outsourcing were uncovered. Access to technical expertise and flexibility were both in first place, followed by cost savings and lack of internal resources in joint second and access to local expertise, focus on core business value chain activities and risk mitigation in shared third. South African organisations identify service providers through four (4) mechanisms: firstly a request for proposals (advertising), direct approach in second and associate recommendations and third-party search in joint third. Seventeen (17) characteristics were identified that influence the selection of a service provider. Of greatest weight is references/reputation, relevant experience, the amount of fee charged and technical expertise in joint first. In joint second; local experience, understanding the client’s organisation, flexible service terms, integrity of approach, regulatory compliance and business values and ethos. This is followed by service provider capacity, individual capability, unconflicted, strong management capability, transparency, strong advisory capability and trust in shared third. The majority of the organisations judged CREM outsourcing successful and twelve (12) attributes were identified that impact the success of CREM outsourcing. Strong advisory capability dominated the list, followed by understanding the client’s organisation and technical expertise in mutual second place. In shared third place, unconflicted, strong management capability, professional integrity, market knowledge value-add, delivering the pledged service, flexible service terms, responsiveness, cost savings and transparency. Practical Implications – A strengthened and grounded understanding of the considerations of non-real estate private organisations in South Africa within the process of CREM outsourcing, will provide an empirical foundation upon which service providers may base their strategic positioning within the local market.